Negative equity companies in Europe: theory and evidence - Urionabarrenetxea, Sara; San-Jose, Leire; Retolaza, Jose-Luis (Business: Theory and Practice, 2016)
Businesses in technical bankruptcy are part of the European context, many of them in such financial distress that they have lost all their equity and a very high percentage of them have even incurred negative equity. There is a very little literature analysing these companies; moreover, they are considered as out of the ordinary because they do not fit into conventional theories of business, and are removed from most samples. They are largely neglected. The research questions posed here are a step towards remedying this: “What are the scale and the economic impact of negative equity companies in terms of risk transference?”, “Does this problem differ from one European country to another?”, “Is it an effect of the crisis?”. Using the Bureau Van Dijk’s Amadeus database, we find that nearly 20% of companies have negative equity. Such companies handle more than one billion Euros, i.e. nearly 10% of European GDP. So the results suggest that negative equity companies have a high weight in Europe and, based on the country cluster studied, it seems that neither culture nor geographical area is determinant in explaining their distribution across countries. Nor is the crisis a determinant in explaining their existence, so the problem is not cyclical but structural. These findings have potentially important implications in encouraging European decision makers to factor such companies into their policies and to include them in economic models.